(untitled) (Informatica, 2014)
When deploying a new mobile technology such as LTE, it is crucial to identify the factors that affect the radio network in terms of capacity and quality of service. In this context, network coverage is arguably the single most influential factor. This work presents a metaheuristic-optimization approach that automatically adapts the parameters of a signal-propagation model. The optimization procedure is performed per cell, enabling the calculation of accurate network-coverage predictions. The evaluation of the proposed approach is carried out on two different regions in Slovenia, where Telekom Slovenije, d.d., provides LTE coverage. The results show radio-propagation predictions of improved quality when compared to manual and analytical methods.